Recent Publications (Quarterly Journal of Economics, 1968)
Recent Publications Get access The Quarterly Journal of Economics, Volume 82, Issue 2, May 1968, Pages 346–348, https://doi.org/10.1093/qje/82.2.346 Published: 01 May 1968